Accidental impoliteness and digital deference - Celiacika Gustisiwi Puteri; Moh. Ruzin; Pedja Rifki Azizi (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2025)
In an increasingly globalized academic landscape, understanding the pragmatic dynamics of EFL classroom interactions in culturally nuanced contexts like Indonesia is essential. This study offers an exploration of the interplay between politeness and impoliteness strategies within the hierarchical and communal culture of an Indonesian higher education setting. Using a qualitative case study design, the research was conducted at a public university in East Java, involving one lecturer and 50 first-year students. Data were collected through video recordings of classroom interactions, followed by transcription and coding using a framework based on Brown and Levinson’s politeness theory and Culpeper’s model of impoliteness. Findings indicate that while positive politeness predominates to foster a collaborative atmosphere, a unique pattern of accidental impoliteness emerges among freshmen. This lack of pragmatic awareness suggests that impoliteness in this context is not a tool for social friction, but a byproduct of the transitional struggle between secondary school norms and university expectations. These findings imply that EFL pedagogy in Indonesia must go beyond linguistic accuracy to include explicit pragmatic instruction. Specifically, there is a need for curriculum adjustments that help students navigate the socio-cultural expectations of higher education to prevent unintentional communication breakdowns in the classroom.